A Critical Study of the Minister of Youth and Sports Regulation No. 14 of 2024: Its Implications for Sport Governance in Indonesia - Maidani; Triana Yuniati (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
Sport governance is an important aspect in creating a transparent, accountable and effective sport management system. However, Indonesia still faces various challenges in its implementation, such as the lack of transparency, weak financial supervision, and government intervention in sports organizations. To address this, the government issued Minister of Youth and Sports Regulation No. 14 of 2024, which aims to improve the governance standards of performance sports organizations. This regulation emphasizes transparency and accountability, but it also raises controversy regarding the potential for government intervention in sports organizations, which is contrary to the principles of the Olympic Charter. This research aims to critically examine Permenpora No. 14 of 2024, by assessing its implications for sport governance in Indonesia and comparing it with regulations in the UK, Australia and China. Using a qualitative approach with policy analysis and case study methods, this research analyzes the content of the regulation, evaluates its conformity with international standards, and identifies implementation challenges. The results show that although the regulation aims to improve sport governance, its implementation faces obstacles in the form of excessive government intervention, limited resources at the organizational level, and potential conflicts with international sport governance principles. Compared to the UK and Australia's more incentive-based and independent oversight, Indonesia's regulatory model tends to resemble China's approach, which gives greater control to the government. Therefore, policy revisions are needed to ensure a balance between transparency, accountability and independence of sport organizations to create more effective and sustainable governance.